Ketimpangan Sosial dalam Ekonomi Digital: Analisis Multidimensional terhadap Akses dan Inklusi Sosial - Pratama, Ahmad Rizky; Ramadhani, Siti Nurhaliza; Santoso, Muhammad Fajar (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital transformation has become a major driver of global socio-economic change while simultaneously generating new forms of social inequality within the digital economy. These inequalities extend beyond unequal access to digital technologies and encompass disparities in digital skills, usage, and the capacity of individuals and social groups to benefit from digital economic opportunities. This article aims to analyze social inequality in the digital economy through a multidimensional approach focusing on access, usage, digital skills, and social inclusion. The study employs a systematic literature review of reputable international academic journals addressing digital inequality and social inclusion. The findings indicate that digital inequality is closely intertwined with socioeconomic factors such as income, education, gender, and geographical location, thereby reinforcing social exclusion among marginalized groups. Furthermore, the results demonstrate that policies centered solely on infrastructure provision are insufficient to address structural digital inequalities. This study concludes that reducing social inequality in the digital economy requires holistic, context-sensitive, and justice-oriented policy interventions to foster sustainable digital inclusion.